How Credibility Endorser Strengthen Brand Equity: Case Study in Shoppe Consumers - Siti Nur Laily Rohmawati (Profesional Muda Cendekia Publishing, 2020)
The background of this study is the difference in research results, wherein the research conducted by Dewi (2017) where endorser credibility does not affect brand equity. While Spry (2011) and Sondakh (2015) endorser credibility have a significant effect on brand equity. This study aims to analyze the effect of endorser credibility on brand equity. The research sample is Post Millennial Shopee consumers with 100 respondents. The sampling technique uses probability sampling. Data processing and hypothesis testing using path analysis. The results showed that Endorser credibility affected brand credibility. Endorser credibility affects brand. Brand credibility affects brand equity, and Brand credibility mediates endorser credibility towards Brand equity.